2018
DOI: 10.1097/inf.0000000000002015
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Tuberculin Skin Tests and Interferon-γ Release Assays in Children Younger Than 5 Years

Abstract: Background: Available data to assess the optimal diagnostic approach in infants and preschool children at risk of tuberculosis (TB) are limited. Methods: We conducted a prospective observational study in children younger than 5 years undergoing assessment with both tuberculin skin tests (TST) and QuantiFERON-TB Gold In-Tube (QFT-GIT) assays at 2 tertiary TB units in Barcelona, Spain. Results: A total of 383 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Diagnostic workup should begin with obtaining sputum samples, most commonly via gastric aspiration for the detection of: TB DNA via polymerase chain reaction (PCR), TB culturing, and TB acid-fast staining. PCR detection yields the highest likelihood to be consistently positive (67%), while positive results for cultures and acid faststaining range between 24%-40% and 10%-50%, respectively, across various studies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic workup should begin with obtaining sputum samples, most commonly via gastric aspiration for the detection of: TB DNA via polymerase chain reaction (PCR), TB culturing, and TB acid-fast staining. PCR detection yields the highest likelihood to be consistently positive (67%), while positive results for cultures and acid faststaining range between 24%-40% and 10%-50%, respectively, across various studies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence on the use of IGRA in children under 5 years old; some studies have found a high level of reproducibility with TST and high specificity, whereas others cite the problems of low reproducibility and low sensitivity . While noting the low‐quality evidence, the guidelines for diagnosing LTBI for under‐5‐year‐olds from the American Thoracic Society, Infectious Disease Society and Centre for Disease Control recommend the use of TST and accept both TST and IGRA results …”
Section: Discussionmentioning
confidence: 99%
“…The reliability of IGRAs among young children are not yet welldefined and increased frequency of indeterminate results in children <5 years limits its use in the detection of LTBI in these children (29). TST+/QFT-discordant results are common, and it remains uncertain if this constellation indicates TB infection or not (30). To overcome misdiagnosis in BCG-vaccinated young children, tested for LTBI, Pavic et al recommended using both tests and considering the child infected if either or both are positive (31,32).…”
Section: Igra Testingmentioning
confidence: 99%